Pengaruh Risk Based Capital Terhadap Profitabilitas Pada Perusahaan Asuransi Jiwa Syariah - Adin Fadilah; Alvido Zakaria, Mochamad Alvido Zakaria (WADIAH, 2025)
This study examines the impact of Risk Based Capital (RBC) on the profitability of Islamic life insurance companies in Indonesia. RBC is a key financial health indicator ensuring insurers can meet their obligations. Using a quantitative approach with panel data regression, the study finds that while RBC influences profitability, the effect is not significant. Other factors such as claim expenses and investment returns must be considered to enhance profitability.